Intelligence Report on the Kaka-Ntem Area of the Bamenda Division of the Cameroons Province (Colonial Letters and the Contact of Knowledges, 1932)
This file contains colonial intelligence report on the Kaka-Ntem Area of the Bamenda Division of the Cameroons Province
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Colonial Intelligence Report; Kaka-Ntem; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies